Quantifying flows and economies of informal e‐waste hubs: Learning from the Israeli–Palestinian e‐waste sector. Issue 1 (4th September 2018) - Davis, John‐Michael; Garb, Yaakov
Abstract : Despite increasing academic attention and the pressing development and environmental importance of informal e‐waste economies in the global South, there remains a dearth of reliable quantitative data to guide theory and appropriate policy responses. We illustrate this problem through a review of the thin and patchy data presented in existing studies that attempt to quantify the flows and economic impact of informal e‐waste hubs. We then describe a way forward through our analysis of a less well known e‐waste hub in south‐west Hebron, Palestine, which provides a methodological model for robust and systematic quantification. We achieved this by leveraging the relatively closed regional‐geographic nature of this hub, triangulating several approaches used in studies of the informal economy (anecdotal/ethnographic, micro‐ and macro‐level data), and contrasting data before and after a key shift in the sector. Our study shows how this hub, though barely registering in official economic and trade data, houses a large, vital and differentiated cluster of businesses, which have processed almost half of Israel's e‐waste for over a decade, and constitute an important export sector and local economic contributor. In 2015, even operating at levels 40% below those sustained over the prior decade, the hub imported and processed 16–25, 000 tonnes of e‐waste, creating 381 enterprises, 1, 098 jobs and US28.5 million gross value added to the Palestinian economy. This study demonstrates methodological approaches for studying informal e‐waste flows and economies and the substantive insights these produce, and argues for the relevance of both to analogous hubs across the global South. Abstract : Despite increasing academic attention and the pressing development and environmental importance of informal e‐waste hubs in the global South, there remains a dearth of careful quantitative data to guide theory and appropriate policy responses. We illustrate this problem through a review of the thin and patchy data presented in existing studies, and describe a way forward through a systematic analysis of a less known e‐waste hub in south‐west Hebron, Palestine. Our study triangulated detailed data from a stratified sample drawn from a comprehensive sampling frame of all businesses in the hub, with data collected at key input and output nodes, thereby producing a robust quantification of volumes, sources, and economic contribution of the industry, with important policy implications.